2012
DOI: 10.1007/s10704-012-9727-x
|View full text |Cite
|
Sign up to set email alerts
|

Interface crack initiation at V-notches along adhesive bonding in weakly bonded polymers subjected to mixed-mode loading

Abstract: In this paper, interface crack initiation at V-notches along adhesive in bonded Polycarbonate (PC) and Poly Methyl Methacrylate (PMMA) subjected to mixed-mode loading conditions was investigated based on a combined experimental, finite element and matched asymptotic analysis. The V-notch specimens with an adhesive interface starting from its tip made at different notch angles were tested under threepoint bending conditions. The experimental observations show that the specimens mainly fail by cracks along the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…As a result, material properties at the interface are different from those of the bulk materials. Indeed, the authors developed a failure mechanics model to analyze crack initiation of a notch which is connected to an interface [21]. Application of this model to 3D printed polymers would be our future research.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, material properties at the interface are different from those of the bulk materials. Indeed, the authors developed a failure mechanics model to analyze crack initiation of a notch which is connected to an interface [21]. Application of this model to 3D printed polymers would be our future research.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of the notch angles on the material strengths was extensively studied by the authors and other researchers [15][16][17][18][19][20][21]. Carpinteri found that the measured strengths of Polymethyl Methacrylate (PMMA) beams with different notch angles were an increasing function of the notch angles as shown in Figure 2 [20].…”
Section: Influence Of the Notch Angle On The Materials Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Tran et al [127] adopted a similar macro-scale approach to predict the failure load of PC/epoxy/PC and PMMA/epoxy/PMMA joints, thus quantifying the influence of the corner angle with good accuracy.…”
Section: Finite Fracture Mechanicsmentioning
confidence: 99%
“…Yosibash et al [36] discussed a failure criterion for predicting failure in brittle materials subjected to mixed-mode loading. Recently, Leguillon extended his failure criterion to a general form for a notch as [28]:…”
Section: Introductionmentioning
confidence: 99%